The effect of exercise on interferon gamma, body fat and bmi of kidney transplant patients - Shakoor, Elham; Salesi, Mohsen; Jahromi, Maryam Koushkie; Sadeghi, Hassan; Karimi, Mohammad Hossein; Yusof, Ashril (Sociedade Brasileira de Medicina do Exercício e do Esporte, 2018)
Introduction: Poor physical function and obesity are well documented in kidney transplant patients. Significant health benefits result from regular physical activity, many of which are important for kidney transplant patients. Objective: The aim of this study was to investigate the effects of 10-week combined exercises on Interferon Gamma (IFNγ), body fat percentage (BF%) and body mass index (BMI) in kidney transplant patients. Method: In a randomized controlled experimental design, 44 kidney transplant patients aged 20-50 years were randomly divided into two groups of exercise (n=23) and control (n=21). The exercise group participated in a cumulative training program for 10 weeks, three days a week, 60–90 minutes per day at 40-65% of predicted maximal heart rate reserve. A 5 ml venous blood sample and anthropometric parameters were taken from the subjects at baseline and after 10 weeks. Results: The exercise group showed an improvement in BF% (from 31.80±5.64 to 28.86 ± 5.82, p =0.001) and BMI (from 26.23 ± 1.81 to 25.45 ± 2.11, p = 0.001), but there was no significant change in the IFNγ level (from 0.06 ± 0.02 to 0.06 ± 0.02, p = 0.829). There was a significant difference between the control and exercise groups for BF% (p = 0.001) and BMI (p = 0.001). Conclusion: As a take-home message, it should be mentioned that combined exercise intervention is inexpensive and portable and can be performed at home or health centers for kidney transplant patients to reduce their weight and BF%. Evidence Level I; High quality randomized trial with or without statistically significant difference, but with narrow confidence intervals.